Rise and fall of nations forces of change in post crisis World - Sharma, Ruchir (New York, W. W. Norton & Company, 2020)
The crisis of 2008 ended the illusion of a golden era in which many people imagined that prosperity and political calm would continue to spread indefinitely. In a world now racked by slowing growth and mounting unrest, how can we discern which nations will thrive and which will fail?
Includes bibliographical references and index.
Keywords: Economic history--21st century